Assessing the Usability of a Prediabetes Self-Care Application: a Multi-Method Approach - Subramaniam, Suthashini; Dhillon, Jaspaljeet Singh (International Journal of Engineering and Technology, 2018)
Increasing demand for digital technology, worldwide, has unlocked new pathways for diabetes prevention. Health behavioural change theories when integrated in the design of novel health applications can foster effective self-health management and prevention. We developed i-PreventDiabetes, a self-care application for prediabetics, that enables lifestyle monitoring, goal setting and activity planning, which is accessible via both web and mobile. In this study, we evaluated the usability barriers and enablers, and assessed the user experience with the system by using a multi-method approach with 20 participants. This approach includes cognitive walkthrough, think-aloud method, question-asking protocol, System Usability Scale (SUS), User Experience Questionnaire (UEQ), and open-ended questions. The results indicate that the users are satisfied with the concept of preventing diabetes by using a self-care application that includes a variety of functionalities that empowers prediabetics to take charge of their own lifestyle in preventing diabetes.
Keywords: Behavioural change theories; Diabetes prevention; Digital health technology; Prediabetes; Self-care; System usability; User experience.